Exploration of aggressive behavior among adolescent in Indonesia - Afdal Afdal; Miftahul Fikri; Nurmaida Pane; Wiwin Andriani (Universitas Negeri Padang, 2020)
Aggressive behaviour is one of the problems which have a negative impact on adolescents, especially on their development process. This study aims to determine the extent to which students' aggressive behaviour is predictable by gender and domicile origin. The participants of this study were a total of 2681 Indonesian teenagers aged 14-20 years, that anonymously and voluntarily filled out this instrument. The instrument used was the AF Aggressive Behaviour Instrument Scale (AFABIS), which has been tested for validity and reliability with a significance of 0.08. Furthermore, data testing was carried out using network psychometrics and Rasch analysis. The results from the network psychometrics analysis showed that there was a good structure of participants in terms of gender and domicile origin (city, suburban, rural) and a significant difference in aggressive behaviour as seen from the sparsity that was raised. The results showed that male adolescents tend to show more aggressive behaviour compared to females. Furthermore, it showed that the tendency of displaying aggressive behaviour by adolescents in rural areas is more tenuous compared to those in suburbs of cities and cities. These results may be used as initial data by counselors for psychological intervention on aggressive behaviour featured by adolescents.